Performance-Based Specifications and Control of Concrete Durability State-of-the-Art Report RILEM TC 230-PSC - Beushausen, Hans.; Fernandez Luco, Luis.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This work gives an overview of significant research from recent years concerning performance-based design and quality control for concrete durability and its implementation. In engineering practice, performance approaches are often still used in combination with prescriptive requirements. This is largely because, for most durability test methods, sufficient practical experience still has to be gained before engineers and owners are prepared to fully rely on them.   This book, compiled by RILEM TC 230-PSC, is intended to assist efforts to successfully build the foundation for the full implementation of performance-based approaches through the exchange of relevant knowledge and experience between researchers and practitioners worldwide.  .
Preface -- 1. Introduction, by H. Beushausen -- 1.1 Background to the work of TC 230-PSC -- 1.2 Terminology -- References -- 2. Durability of Reinforced Concrete Structures and Penetrability, by L.-O. Nilsson, S. Kamali-Bernard, M. Santhanam -- 2.1 Introduction -- 2.2 Mechanisms Causing Reinforcement Corrosion -- 2.3 Concrete Properties Relating to the Ingress of Aggressive Agents -- 2.4 Service Life and Deterioration Models (Principles) -- References -- 3. Prescriptive Durability Specifications, by R. Torrent, R. d'Andrea, A. Gonçalves, F. Jacobs, K. Imamoto, A. Kanellopoulos, M. Khrapko, A. Monteiro, S. V. Nanukuttan -- 3.1 Introduction -- 3.2 Exposure Classes -- 3.3 Materials -- 3.4 Service Life -- 3.5 Concrete Strength Grades -- 3.6 Mix Composition Prescriptions -- 3.7 Contribution of Supplementary Cementitious Materials -- 3.8 Cover Depth Prescriptions -- 3.9 Concrete Practices -- 3.10 Compliance/Conformity Control -- 3.11 Discussion and Conclusions -- References -- 4. Test Methods for Concrete Durability Indicators, by D. Bjegović, M. Serdar, I. S. Oslaković, F. Jacobs, H. Beushausen, C. Andrade, A. V. Monteiro, P. Paulini, S. Nanukuttan -- 4.1 Introduction -- 4.2 Gas Permeability -- 4.3 Water Permeability -- 4.4 Capillary Absorption -- 4.5 Chloride Penetration -- 4.6 Concrete Resistivity and Conductivity -- 4.7 Final Remarks -- References -- 5. Principles of the Performance-Based Approach for Concrete Durability, by H. Beushausen, M. G. Alexander, M. Basheer, V. Baroghel-Bouny, R. d'Andrea, A. Gonçalves, J. Gulikers, F. Jacobs, M. Khrapko, A. V. Monteiro, S. V. Nanukuttan, M. Otieno, R. Polder, R. Torrent -- 5.1 Introduction -- 5.2 Pre-Qualification versus Compliance Control -- 5.3 Performance-Based Design and Specification (Pre-Qualification) -- 5.4 Performance-Based Quality Control and Compliance Assessment -- 5.5 Environmental Actions (Quantification) -- 5.6 Development of Limiting Values for Specification and Compliance Control -- References -- 6. Statistical Procedures for Performance-basedSpecification and Testing, by Werner A. Stahel, Fabrizio Moro, Luis Fernandez Luco -- 6.1 Introduction -- 6.2 Distributions -- 6.3 Basic statistical inference -- 6.4 Analysis of variance and regression -- Bibliography -- 7. Responsibilities, by D. Hooton, M. Khrapko, M. Otieno, M. Ismail -- 7.1 Introduction -- 7.2 Performance-Based Durability Limits -- 7.3 Verification of Durability -- 7.4 Quality Management using Performance-Based Specifications -- 7.5 Responsibilities of the Owner/Specifier, Contractor and Supplier/Producer -- 7.6 Conclusion -- References -- 8. Application Examples of Performance-Based Specification and Quality Control, by H. Beushausen, M. G. Alexander, C. Andrade, M. Basheer, V. Baroghel-Bouny, D. Corbett, R. d'Andrea, A. Gonçalves, J. Gulikers, F. Jacobs, A. V. Monteiro, S. V. Nanukuttan, M. Otieno, R. Polder and R. Torrent.- 8.1 Introduction -- 8.2 Site Air-Permeability ("Torrent Method") -- 8.3 Oxygen Permeability Index (South Africa) -- 8.4 Autoclam Permeability System (UK) -- 8.5 Service Life Prediction using Concrete Resistivity (Spain) -- 8.6 Surface Resistivity (USA) -- 8.7 Two Electrode Resistivity Method (the Netherlands) -- 8.8 Chloride Conductivity Index (South Africa) -- 8.9 Rapid Chloride Migration Test (suggested for Application in the Netherlands) -- 8.10 In Situ Ionic Migration Test: PERMIT (UK) -- 8.11 Multi-Level Prediction of Reinforced Concrete (RC) Durability -- 8.12 Portuguese Technical Specifications -- References -- 9. Basis for the Statistical Evaluation of Measured Cover Depths in Reinforced Concrete Structures, by A. V. Monteiro, A. Gonçalves, J. Gulikers and F. Jacobs -- 9.1 Definitions -- 9.2 Introduction -- 9.3 Procedure A: Inspection by Variables -- 9.4 Procedure B: Inspection by Attributes -- 9.5 Procedure C: Inspection by Attributes - Large Lots -- 9.6 German Code of Practice -- 9.7 Actions in the Case of Non-Conformity -- 9.8 Examples -- 9.9 Final Remarks -- References -- Appendices to Chapter 9 -- A9.1 Construction of Probability Plots and Detection of Potential Outliers -- A9.2 Definition of the Lower One-Sided Tolerance Limit [12] -- A9.3 Dealing with Spatial Autocorrelation -- A9.4 Construction of OC Curves [12] -- 10. Venlo Application Testing (summary), by L. Fernandez Luco, H. Beushausen, F. Jacobs, M. Serdar -- 10.1 Introduction -- 10.2 Summary of test results -- 10.3 Further assessment from compiled rankings -- Acknowledgements -- 11. Venlo Application Testing (Individual Reports and Additional Data), by H. Beushausen, L.Fernandez Luco, F. Jacobs, M. Serdar, M. Basheer, S. Nanukuttan, R. Torrent, K. Imamoto -- 11.1 Introduction -- 11.2 Panel Manufacture and Concrete Properties -- 11.3 Air Permeability (OPI) and Chloride Penetration (CCI) -- 11.4 Air-Permeability ("Torrent Method") and Cover Depth -- 11.5 Autoclam Permeability tests -- 11.6 Permit Ion Migration Test -- 11.7 Single Chamber Method -- 11.8 Air Permeability (Packer Test) -- 11.9 Air Permeability (Seal Method) -- 11.10 Water Absorption (SWAT) -- 11.11 References -- 12. Conclusions, by H. Beushausen -- Appendix A: Performance-Based Test Methods and Applications (By Country).
Keywords: Building materials; Security systems; Building Materials; Structural Materials; Security Science and Technology